PEMBERDAYAAN PEMUDA DALAM PERENCANAAN PEMBANGUNAN TEMPAT WISATA DI KAMPUNG BONEN DESA BAUMATA - Sonbai, Debora Elviwanti; Klau, Erni Raster; Neonufa, Samrid (Universitas Nusa Cendana, 2024)
ABSTRACT The aim of this research is to determine the process of youth empowerment through the developmentof tourist attractions in Bonen village, Baumata village using descriptive qualitative research. The results and discussion found that: youth empowerment in planning the development of tourist attractions in Bonen village, Baumata village consists of 2 themes, namely the youth empowerment stage and its indicators: 1). Awareness and behavior formation stage, including empowerment, starting to create initial preconditions by opening people’s awareness of their conditions 2). Ability transformation stage in the form of knowledge and skill, including motivated youth empowering themselves by taking an active role in the development of tourist attractions and 3). The independence stage, including developing the potential for initiative and motivation in creating photo spots. 1). Enabling indicators in the form of potential to be developed 2). Empowering indicators/abilities in the form of knowledge and skill 3). Protecting indicators/increasing ability to overcome problems 4). Supporting indicators/role or involvement in order to become independent and 5). Fostering indicators/ changes obtained. The result is that yout improve the welfareof families in Bonen village through the development of tourist attractions.